Predictors of behavioral health service utilization in a medicaid enrolled sample of emerging adults. (January 2020) - Abraczinskas, Michelle; Bory, Christopher; Plant, Robert
Highlights: Medicaid enrolled emerging adults (EA) utilized behavioral health services differently, depending on diagnosis. Supports are necessary for medicaid enrolled EA s with only Substance Use Disorders and those from minority groups to maintain their service utilization. EA from minority groups were less likely to utilize services at 18 than White EA. Child welfare involved EA had greater odds of utilizing services at age 18 compared to uninvolved EA. Abstract: Emerging adults (EA), individuals between the ages of 15-26, face many challenges in their transition to a new developmental stage, especially those with behavioral health concerns who do not receive the supports they need. Many EA drop out of services at 18, which is likely due in part to the need to transition to the adult service system and the lack of available transition support services in child/adolescent service systems. Though this is a clear disparity, research on EA service utilization, especially those enrolled in Medicaid and with co-occurring conditions, is rare. This paper begins to address this gap by examining variables at age 17 that predict the service utilization of continuously Medicaid enrolled EA at age 18. Data came from an administrative dataset. The sample had 4, 548 EA and 53% were female, 50% identified with a minority group, and 19% were child-welfare involved. Exploratory logistic regression analyses were used. Minority EA had lower odds of utilizing services at age 18. EA involved with child welfare had greater odds of utilizing services at age 18. EA with at least one Substance Use Disorder (SUD) and at least one mental health disorder at 17 had a higher likelihood of service utilization at 18, the opposite was true for EA with only SUDs. These findings identified predictors of service utilization for an understudied sample—EA enrolled in Medicaid. Results provided preliminary evidence that EA with SUD diagnoses access behavioral health services differently than those without a SUD diagnosis, and that it is fruitful to examine subgroups of EA when seeking to understand their service utilization patterns. Identifying predictors of service utilization during the transition period from the child to the adult system can help inform systems interventions to retain EA in services.